Selenium in commercial beer and losses in the brewing process from wheat to beer. (1st September 2015) - Rodrigo, S.; Young, S.D.; Cook, D.; Wilkinson, S.; Clegg, S.; Bailey, E.H.; Mathers, A.W.; Broadley, M.R.
Highlights: The manufacturing of Se-enriched products is now a target of numerous research works. This article presents a great survey about the amount of selenium that the commercial beers contain. This article presents a detailed pathway of selenium losses along the brewing process. This research could provide important information about the selenium intake through the beer. Abstract: There is increasing interest in enhancing the micronutrient composition of cereals through fertilization. The aims of this study were (1) to determine the Se concentration of commercial beers retailing in the UK, and (2) to test if the transfer of Se, from biofortified grain to final beer product, is <10% under UK cultivation conditions, as seen previously under Mediterranean conditions. The Se concentration of 128 commercial beers was measured, using inductively coupled plasma-mass spectrometry (ICP-MS). The selenium content of commercial beers varied 6.5-fold, with beers originating from America having higher Se concentrations than those from Europe. Laboratory-scale brewing trials with isotopically-enriched 77 Se wheat, sampled from UK field-sites, showed that most 77 Se losses in the brewing process occurred during mashing (54%), with fermented beer containing ∼10% of the 77 Se initially present in the wheat grain. Total N values in wort and malt were positively correlated with the 77 Se content of the wheat grain.